Penggunaan Tiga Macam Mulsa Organik dan Tingkat Ketebalan pada Pertumbuhan dan Hasil Tanaman Kedelai (Glycine max (L.) Merrill) Varietas Grobogan - Putri, Meyva Dinda Rutma; Triyono, Kharis; Sumarmi, Sumarmi (JURNAL AGROTROPIKA, 2024)
The research was carried out from October 2023 to January 2024 at the Tohudan Horticultural Seed Garden, Colomadu District, Karanganyar Regency. This research used a Polynomial Split Plot Design consisting of 2 treatment factors, namely the use of three types of organic mulch consisting of 4 levels, namely M0 (control) plastic mulch, M1 (rice straw mulch), M2 (banana stem mulch), M3 (stem corn mulch) and the level of mulch thickness consisting of 3 levels, namely T1 (1 cm thickness), T2 (2 cm), T3 (3 cm). The results showed that the banana stem mulch treatment with a thickness of 3 cm gave the best results for soybean growth with a plant height of 106.67 cm and a number of leaves of 102.33. Banana stem mulch treatment with a thickness of 1 cm gave the best results for the growth of soybeans with a leaf area of 103.00 m2. Banana stem mulch treatment with a thickness of 2 cm gave the best yield of soybean with a number of pods of 87.00 pods, a number of seeds of 215.67, a seed weight of 27.67 grams, a weight of 100 seeds of 10.00 grams. The treatments of plastic mulch and organic mulch of 3 cm thickness provide the best results for suppressing weed growth.  Keywords: plastic mulch, organic mulch, thickness, soybean